Video-Assisted Thoracic Surgery in Early Stage of Pediatric Pleural Empyema Improves Outcome - Pogorelić, Zenon; Bjelanović, Dora; Gudelj, Ružica; Jukić, Miro; Petrić, Jasna; Furlan, Dubravko (The Thoracic and Cardiovascular Surgeon, 2020)
Objectives The aim of this study was to observe outcomes of early decortication in a treatment of pleural empyema using video-assisted thoracoscopic surgery (VATS).Methods The case records of 21 pediatric patients who underwent VATS for empyema between 2009 and 2019 were retrospectively reviewed. Patients were observed based on demographic, laboratory, and clinical data, as well as treatment outcomes.Results Out of a total of 59 patients treated for pleural empyema, 21 (10 male and 11 female) children with a median age of 5 years (interquartile range [IQR] 2.8; 6.0) received VATS. The empyema was classified as stage I in 2 patients (9.5%), stage II in 4 patients (19%), and stage III in 15 patients (71.5%). Median surgical time was 60 minutes (IQR 50; 90). There were 2 (9.5%) postoperative complications and 1 recurrence (4.8%). Children treated in stages I and II showed significantly better postoperative results compared with the children treated in stage III. Length of hospital stay (8 vs. 10 days; p = 0.01), length of intensive care unit stay (1 vs. 5 days; p < 0.001), duration of chest tube drainage (4 vs. 6 days; p = 0.043), duration of postoperative fever (1.5 vs. 4 days; p = 0.001), and surgical time (40 vs. 70 minutes; p < 0.001) were significantly shorter in children operated in stages I and II than in stage III.Conclusion Early decortication using a VATS is a successful, effective, and easily performed surgical method in the treatment of pediatric pleural empyema, as well as a method that significantly improves recovery time and shortens the hospital stay.
Keywords: empyema; VATS; early decortication; children; thoracoscopy